A review on biochar’s effect on soil properties and crop growth - Premalatha, R. P.; Poorna Bindu, J.; Nivetha, E.; Malarvizhi, P.; Manorama, K.; Parameswari, E.; Davamani, V. (Frontiers in Energy Research, 2023)
Feeding the growing world population relies on the agricultural production. Intensive cultivation of agricultural soils causes soil degradation which emphasizes the need for sustainable soil management. Biochar, a pyrolysed carbon rich material has gained great interests among the researchers because of its eco-friendly benefits in addition to soil quality enhancement. Their properties like pH, greater surface area, cation exchange capacity, and nutrient content positively influences the soil properties and ultimately improves the soil fertility. But its effect is not the same in all soil types. It has been found to be more effective in acid soils than the alkaline or calcareous soils. In this review, the effect of biochar application on soil properties (physical, chemical, biological), remediation of heavy metal contaminated soils and crop productivity are discussed in detail.